World Economy Winter 2024: Strong headwinds for global economic activity - Klaus-Jürgen Gern; Stefan Kooths; Wan-hsin Liu; Jan Reents; Nils Sonnenberg (Kiel Institute for the World Economy (IfW Kiel), 2024)
The global economy is facing increased economic policy uncertainty in a phase of already moderate momentum. The announcements made by the incoming US administration are the main reason for this. However, it is unclear what measures will actually be taken. This forecast is based on the assumption that additional tariffs will be imposed on imports into the United States, but that these will not be as extensive as has been suggested during the election campaign. While we assume that the decline in US policy interest rates will be slowed, we still expect that global economic activity will gradually receive tailwinds from more favorable financing conditions. Under these assumptions, the US economy is likely to continue to expand significantly, while economic momentum in Europe will gradually pick but remain low. At the same time, a sustained economic recovery in China is still not in sight despite the announced stimulus measures given the gloomy outlook for exports. While global trade has showed signs of life in the year to date, it is likely to be slowed noticeably over the forecast horizon by the expected restrictive trade policy measures. All in all, we keep our forecast for global output growth in 2024 - measured on a purchasing power parity basis - to at 3.2 percent this year. For next year, we expect an expansion of 3.1 percent, also unchanged from our September forecast. The outlook for 2026 has deteriorated and we have reduced our forecast by 0.2 percentage points to 3.1 percent. The decline in inflation has slowed down of late, and the lack of a year-on-year fall in energy prices and the expected further decline in inflation towards the target of 2 percent is likely to be sluggish mainly due to the persistent rise in services prices. There is a risk that monetary policy will remain restrictive for longer than currently expected. In addition, there are still major risks for the global economy from a possible escalation of geopolitical conflicts. Trade conflicts could also escalate further, but they could also turn out to be less severe than assumed.
Keywords: 330; China; USA; Business Cycle World; Growth; Europe; International Finance